PERGESERAN RELASI GENDER PEREMPUAN SAMIN (STUDI TENTANG PEMBAGIAN KERJA DALAM MASYARAKAT SAMIN DESA KEMANTREN KABUPATEN BLORA) - Choir, Abu; Aijudin, Anas; Mibtadin, Mibtadin; Hermawan, Sulhani (Forum Ilmu Sosial, 2012)
Socio-cultural changes that occurred in the Samin community has changed gender relations and division of labor system Samin community. This paper aims to clarify the role of women in the past Samin and the role of women in the present Samin. In the past, the role of women Samin confined to household work, do not have public access, and restrictions on education. At present, women Samin has been engaged in productive and reproductive work, and has been active in social activities. Samin female gender relations shift occurs due to internal factors, namely a change of mind and improvement of the economy, as well as external factors namely the development of information technology and transportation in their lives. This shift in gender roles also occurred due to the role of several actors, such as village officials, religious leaders, and community agencies.